The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/ijc.22132
|View full text |Cite
|
Sign up to set email alerts
|

Acute apoptosis by cisplatin requires induction of reactive oxygen species but is not associated with damage to nuclear DNA

Abstract: Cisplatin is a broad-spectrum anticancer drug that is also widely used in experimental studies on DNA damage-induced apoptosis. Induction of apoptosis within 24-48 hr requires cisplatin concentrations that are at least one order of magnitude higher than the IC 50 . Here, we show that such high, apoptosis-inducing cisplatin concentrations induce cellular superoxide formation and that apoptosis is inhibited by superoxide scavengers. The same concentration limit and the requirement for superoxide are also true f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(188 citation statements)
references
References 29 publications
14
162
1
1
Order By: Relevance
“…Interestingly, Pt-adduct formation was reduced markedly in hypoxic cells exposed to oxaliplatin, which could contribute to the observed differential toxicity. Treatment of cells with oxaliplatin at concentrations greater than clonogenic IC 50 suggested that apoptosis was dependent on the generation of reactive oxygen species (Berndtsson et al, 2007), which would be compromised in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pt-adduct formation was reduced markedly in hypoxic cells exposed to oxaliplatin, which could contribute to the observed differential toxicity. Treatment of cells with oxaliplatin at concentrations greater than clonogenic IC 50 suggested that apoptosis was dependent on the generation of reactive oxygen species (Berndtsson et al, 2007), which would be compromised in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…However, as observed in carcinomas, elevated doses of DNA-damaging agents tend to induce apoptosis not just as a result of DNA damage but rather as an "off-target effect" (37). Instead, an increasing body of evidence indicates that cells tend to respond to low doses of DNA-damaging agents activating a senescent pathway rather than death pathways (22,38,39). It has been postulated that in cells treated with cytotoxic drugs, senescence and cell death are concurrent responses characterized by different kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the topoisomerase inhibitor etoposide (Oh et al, 2007), arsenic trioxide (Nakagawa et al, 2002), and cisplatin (Berndtsson et al, 2007) all induced cell death in various cancers through oxidative stress.…”
Section: Additional Examples Of Rons-mediated Cancer Prevention: N-3 mentioning
confidence: 99%